THE IMPACT OF COAL MINING ON THE SOCIO-ECONOMIC CONDITIONS OF THE COMMUNITY IN SANGATTA, EAST KUTAI REGENCY - Ludia, Febriana; Fermita, Blesscia Senia; Putri, Dina Hayati; Rahmawati, Dewi (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research aims to analyze the impact of coal mining on the social, economic, and environmental conditions of communities in Sangatta District, East Kutai Regency. Mining, as one of the key sectors driving regional economic development, also brings about various issues related to social change, economic inequality, and environmental degradation. The research method employed is a survey with a quantitative approach, namely the collection of measurable numerical data that can be statistically analyzed through questionnaires. The study involved 30 respondents determined by purposive sampling, that is, deliberate selection based on specific criteria namely, residents living around the mining area who are considered to be most affected. The results show that 66.67% of respondents were in the age range of 19-31 years, with the majority stating that they benefited economically from increased job opportunities (76.67%), followed by improvements in local businesses (13.33%) and infrastructure development (6.67%). In terms of social aspects, most respondents (46.67%) assessed that the level of crime or social problems remained the same, although 6.67% perceived an increase. Meanwhile, from the perspective of regional economy, 70% of respondents noted a significant rise in land and property prices, ranging from 50-100% or even higher. The environmental impacts reported by the community include air pollution, land degradation, and disruption of water resources. This indicates that although mining provides economic contributions to most residents, there are also consequences in the form of social inequality and environmental pressures. Therefore, more sustainable mining management is needed, taking into account the balance between economic benefits, social stability, and environmental sustainability.